Prognostic parameters of in‐hospital mortality in COVID‐19 patients—An Italian experience. (29th June 2021) - Ruscica, Massimiliano; Macchi, Chiara; Iodice, Simona; Tersalvi, Gregorio; Rota, Irene; Ghidini, Simone; Terranova, Leonardo; Valenti, Luca; Amati, Francesco; Aliberti, Stefano; Corsini, Alberto; Blasi, Francesco; et al.
Abstract : Abstract: Background: During COVID‐19 outbreak, Italy was the first country in Europe to be heavily affected with an intensive care unit mortality of 26%. In order to reduce this percentage, physicians should establish clear and objective criteria to stratify COVID‐19 patients at high risk of in‐hospital death. Thus, the aim has been to test a large spectrum of variables ranging from clinical evaluation to laboratory biomarkers to identify which parameter would best predict all‐cause in‐hospital mortality in COVID‐19 patients. Design: observational study. Results: Multivariate Cox regression analysis showed that each 5 years of increase in age corresponded to a hazard ratio (HR) of 1.28 (95% CI 1.00‐1.65, P = .050); each increment of 803 ng/L of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) corresponded to a HR of 1.24 (95% CI 1.11‐1.39, P < .001); each increment of 58 ng/L of interleukin (IL)‐6 corresponded to a HR of 1.23 (95% CI 1.09‐1.40, P < .001), and each increment of 250 U/L of lactate dehydrogenase (LDH) corresponded to a HR of 1.23 (95% CI 1.10‐1.37, P < .001). According to the calculated cut‐points for age (≥70 years), NT‐proBNP (≥803 ng/L), IL‐6 (≥58 ng/L) and LDH (≥371 U/L) when 2 out of these 4 were overcome, the HR was 2.96 (95% CI 1.97‐4.45, P < .001). Conclusion: In COVID‐19 patients, besides age, the evaluation of three biochemical parameters, available in few hours after hospital admission can predict in‐hospital mortality regardless of other comorbidities.